O conceito de natureza como ponto de divergência entre a ética epicurea e a ética estoica - Santos, Rogério Lopes dos (2019)
The present thesis aims at showing that the Stoic conception of human nature emerges as a point of divergence with the epicurean conception of human nature, and that from this divergence we have the cause of the distortion of the Epicurean Ethics made above all by the named ‘early Christian philosophers’. That way, we divided the thesis into three parts: a) the first part is devoted to the presentation and analysis of the concept of Nature in Stoicism, on the following points of investigation: (i) on the way the concept of Nature is conceived in the stoic Philosophy; (ii) on the origins and divergences of Stoic thought regard to the equation between ‘living according to Nature’ and virtuous being; (iii) Stoic criticism as to the enjoyment of pleasure in wise life; b) the second part of the thesis deals with: (i) epicurean physiology; (ii) Epicurus’ conception of the traditional Greek and Stoic religion; (iii) with pleasure and desire (epithymía) developed by Epicurean Ethics. In this second part we are also concerned with highlighting the points of divergence between Epicurean Philosophy and Stoic Philosophy, as well as to justify the claim that the criticisms and “distortions” made by Christian ‘philosophers’ to Epicurean Ethics were constructed under the basis of the criticisms and “distortions” made by the Stoics; (c) The third and last part of the thesis lies precisely on the ‘attack’ made by Christian ‘philosophers’ on Epicurean Ethics, based primarily on Cyrenaic Ethics as if it were Epicurean. In this context the main opponents of Epicureanism in the ascension times of Christianity are analyzed: Clement of Alexandria, Lactantius, Justin Martyr, Jerome of Stridon and Aurelius Ambrosius.